161k views
5 votes
Solve 5(x + 1) = 5(x + 5) − 15 .

User Leff
by
5.3k points

2 Answers

4 votes
there is no solution
User Riley Carney
by
5.0k points
4 votes

Multiply the first bracket by 5

Multiply the second bracket by 5

5(x + 1) = 5(x + 5) − 15

5x+5=5x+25-15

5x+5=5x+10

Move +5 to the other side. Sign changes from +5 to -5

5x+5-5=5x+10-5

5x=5x+5

Move 5x to the other side. Sign changes from +5x to -5x

5x-5x=5

0=5 ( No solution)

Answer: No solution

User Pubudu Dodangoda
by
5.5k points